2000
DOI: 10.1038/sj.cgt.7700079
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient suicide gene expression in hepatocellular carcinoma cells by Epstein-Barr virus-based plasmid vectors combined with polyamidoamine dendrimer

Abstract: The present study was aimed at devising an efficient nonviral strategy for suicide gene therapy of hepatocellular carcinoma (HCC). To improve the efficiency of DNA delivery and expression, we applied Epstein-Barr virus (EBV)-based plasmid vectors instead of conventional plasmid vectors and combined them with cationic liposome (EBV/lipoplex) or polyamidoamine dendrimer (PAAD) (EBV/polyplex). When the ␤-galactosidase gene was transferred to HuH7, PLC/PRF/5, or HLE cells, Յ50-fold higher ␤-galactosidase activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…By 9 h after calcium was restored, cultures pretreated and infected in calcium-free DMEM supplemented with 100 mM EGTA accumulated fluorescein as well as control cultures (Figure 6b; 9 h), indicating that paracellular junction integrity was restored by this time point. No further change in the pattern of fluorescein accumulation was observed by 24 ( Figure 6b; 24 h), 48 , and 72 h after calcium restoration (data not shown). No differences in fluorescein accumulation were observed whether hepatocyte cultures were mock-infected or infected with baculovirus (data not shown).…”
Section: Rebound Of Paracellular Junction Integrity Following Extracementioning
confidence: 81%
See 1 more Smart Citation
“…By 9 h after calcium was restored, cultures pretreated and infected in calcium-free DMEM supplemented with 100 mM EGTA accumulated fluorescein as well as control cultures (Figure 6b; 9 h), indicating that paracellular junction integrity was restored by this time point. No further change in the pattern of fluorescein accumulation was observed by 24 ( Figure 6b; 24 h), 48 , and 72 h after calcium restoration (data not shown). No differences in fluorescein accumulation were observed whether hepatocyte cultures were mock-infected or infected with baculovirus (data not shown).…”
Section: Rebound Of Paracellular Junction Integrity Following Extracementioning
confidence: 81%
“…Many different gene delivery methods are available including cationic lipid-based DNA transfection [44][45][46][47][48][49] and retroviral and adenoviral gene transfer vectors; [50][51][52][53][54][55] however, the use of these methods for hepatocytes has not been effective because hepatocytes do not divide, are highly susceptible to toxicity, and transfection efficiencies in hepatocytes are extremely low (HC Isom, unpublished data). 11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that use of the EBV-based plasmid vector combined with polyamidoamine dendrimer (PAAD) (EBV/polyplex) resulted in a markedly high expression in human HCC and Ewing's sarcoma cell lines, suggesting the potential usefulness of the EBV/polyplex system for gene therapy. 31,32 However, no study has been reported in which a tumor-specific promoter was employed in the EBVbased plasmid vector to target tumor cells. In this study, we combined the multimerized CEA promoter with the EBV/polyplex system to establish an efficient nonviral strategy to target CEA-producing cancers.…”
Section: T He Prognosis Of Cholangiocarcinoma (Cc) Is Poormentioning
confidence: 99%
“…Four plasmid vectors, pSES.␤, pS.␤, pSES.Tk, and pS.Tk (Figs 2 and 3), have been described previously. 21,31 The other plasmid vectors, pT.␤, pTES.␤, pSET.␤, pTET.␤, pT.Tk, and pTES.Tk (Figs 2 and 3), were constructed by substituting the tetraplicated CEA promoter for the SR␣ promoter in pS.␤, pSES.␤, pS.Tk, or pSES.Tk.…”
Section: Plasmid Vectorsmentioning
confidence: 99%
“…We have applied the EBV-plasmids to various preclinical studies of gene therapy, including those for hereditary, 21 chronic, 22,23 as well as malignant diseases. [24][25][26][27] In some of these studies, the EBV-based plasmid vectors were combined with cationic liposomes, 25,28 cationic polymers, 23,[25][26][27]29 electroporation 21 or gene gun, 30 while in the other studies, naked EBV-based plasmid was injected into the cardiac muscle. 22,29 In the present study, we transferred the naked EBV-based plasmid vectors to the liver through the intravascular route.…”
mentioning
confidence: 99%